Sonohysterographic Predictors of Successful Hysteroscopic Myomectomies - Keltz, Martin D. (JSLS, 2015)
BACKGROUND AND OBJECTIVES: The purpose of this study is to assess the rate of persistent submucosal myomas and intrauterine scarring after hysteroscopic myomectomy, as well as to evaluate the preoperative and intraoperative sonohysterographic findings that will predict persistence of myomas, scarring, and the need for repeat surgery. METHODS: Charts from all hysteroscopic myomectomies performed by a single surgeon between 2003 and 2011 were reviewed for preoperative, intraoperative, and postoperative sonohysterographic findings. Predictors included myoma number, diameter and percent extension into the cavity of the largest fibroid, and percent surgically resected. These predictors were assessed with postoperative sonohysterography. Statistics included t test, logistic regression, χ(2) test, and Fisher exact test. RESULTS: Among the 79 cases with postoperative sonohysterograms, 17 (21.5%) had persistent submucosal myoma, and 9 (11.4%) had intrauterine scarring on postoperative sonohysterogram. Repeat hysteroscopic myomectomy was required in 11 (13.9%), but none required lysis of adhesions. The myoma number was not a significant predictor. A higher percentage of myoma within the cavity (63.35% vs 44.89%, P < .05) and smaller myoma size (2.22 cm vs 3.31 cm, P < .01) were significant predictors of a complete resection, a normal postoperative sonohysterogram, and avoidance of repeat surgery. On regression analysis, the percent of the myoma resected was the most significant outcome predictor (P < .001). CONCLUSION: Larger myomas with a lower percent found within the uterine cavity are less likely to be completely resected. Percent resection at the time of surgery is the most significant predictor of a normal postoperative sonohysterogram, as well as the best predictor of the need for repeat surgery.